พลวัตของแพลงก์ตอนสัตว์ในอ่าวคุ้งกระเบน จังหวัดจันทบุรี - วรพงศ์ ตันติชัยวนิช (จุฬาลงกรณ์มหาวิทยาลัย, 2005)
Study on Zooplankton dynamic in Kung Krabaen Bay, Chanthaburi Province was investigated from March 2004 to January 2005. Zooplankton samples were collected every two months by a 103 um- meshed conical net equipped with a flowmeter from 16 sampling stations in Kung Krabaen Bay and 1 station in the sea. Towing was conducted at day time. As the results indicated that zooplankton composition comprised 40 groups from 15 phyla in which were divided into 22 groups of holoplankton and 18 groups of meroplankton. The average density ranged from 7.69x10 [superscript 5]-1.76x10 [superscript 7] ind. 100 m. [superscript -3] Copepod was a dominant population and contributed to 49.92% of total zooplankton density. Crustacean nauplii, Gastropod larvae, Bivalvia larvae and Larvacean were also found in abundance. Density of Cladocera and Rotifera corresponded to seasonal variation and found in abundance during southwest monsoon season or rainy season because these groups live mainly fresh water and in brackish water. Total density of zooplankton showed higher density in northeast monsoon season than those in southwest monsoon season. The zooplankton communities in the bay had more similarity than those near the mouth of the bay as well as near the mangrove forest. However, the density of larvae of crustacean varied in relation to the transparency of water column significantly (p=0.05). the biological factor such as chlorophyll a was also influent the population densities of Hydromedusae positively. Furthemore, the presence of predator zooplankton such as arrow worm and Hydromedusae and Fish larvae would affect to the density of Copepod, larvae of Mollusk, Polychaete and Crustacean. Brachyuran larvae density was high near the mangrove forest in September and November 2004 because these were breeding and egg laying season of mud crab and blue swimming crab. Therefore, it is necessary to reduce crab harvesting in the period regarding preservation and conservation of natural crab stock. This study also indicates the important role of Brachyuran larvae, Shrimp larvae, Fish larvae and Bivalvia larvae were used as bioindicator for productivity of Kung Krabaen Bay ecosystem.